Trend of Antihypertensive Use and Blood Pressure Control Among Hypertensive Patients in a Tertiary Care Hospital of Kathmandu - Shrestha, Deepti; Shrestha, Shirish L; Poudel, Rekha; Shakya Gurung, Rashmi; Yadav, Radhay Shyam; Shrestha, Lava; Shrestha, Deepti (Journal of Institute of Medicine Nepal, 2022)
Introduction Hypertension is a global burden and prevalence of hypertension increases with age. Various antihypertensive drugs are available for the management of hypertension. The aim of this study is to assess the trend of antihypertensive drugs used and blood pressure (BP) control among patients with hypertension. Methods A cross sectional study was conducted among patients with hypertension prescribed with antihypertensive drugs in Department of Medicine, Nepal Medical College Teaching Hospital. Antihypertensive drugs, number of antihypertensive drugs prescribed in each individual and BP were analyzed. Results Out of 218 patients, 61.5% were female and 38.5% were male. Common age group range from 51-60 years in 28.4% of patients. Diabetes mellitus (23.4%) was the most common comorbid condition. Dual therapy (47.6%) followed by monotherapy (45.9%) was the most common therapy prescribed for patients with hypertension. Most commonly prescribed antihypertensive as monotherapy was Calcium Channel Blockers (CCBs), 29.4% and in dual therapy, CCBs and Angiotensin Receptor Blockers (ARBs), 38.6% were the most commonly prescribed medications. Fixed dose combination of antihypertensive drugs were prescribed in 81.4% among patients receiving multiple therapy. Good BP control was observed in 61.2% of patients with hypertension. Conclusion Dual therapy followed by monotherapy was the most common therapy prescribed for the management of hypertension. Calcium channel blockers as monotherapy and CCBs and ARBs as combination therapy were the most common antihypertensive drugs prescribed for hypertension. More than half the patients had controlled BP. A therapeutic audit with more parameters of analysis to provide regular feedback to researchers and prescribers may encourage rational prescribing in hypertension.